2008
DOI: 10.1029/2008gl034211
|View full text |Cite
|
Sign up to set email alerts
|

Effects of shock‐induced tensile failure on mbMs discrimination: Contrasts between historic nuclear explosions and the North Korean test of 9 October 2006

Abstract: [1] Rayleigh wave excitation is studied for an explosion source model consisting of a superposition of isotropic (monopole), tensile failure, and tectonic release point sources. The body-force representation for shock-induced, deep-seated tensile failure is a compensated linear vector dipole CLVD, where the relative strength of the CLVD is given by an index K. Rayleigh wave amplitudes are reduced owing to destructive interference between an explosive monopole and a CLVD source with vertical axis of symmetry in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 18 publications
(18 reference statements)
1
42
0
Order By: Relevance
“… Patton and Taylor [2008, hereafter PT08] proposed a damage model for shock‐induced, deep‐seated tensile failure that identified extensional deformations along a vertical axis of symmetry and contractions around the waist of the explosion as a cause of damage. Such deformations can be seen in the hydrodynamic flow in frames 5–7 in Figure 1.…”
Section: An Explosion Source Model Accounting For Source Medium Damagementioning
confidence: 99%
“… Patton and Taylor [2008, hereafter PT08] proposed a damage model for shock‐induced, deep‐seated tensile failure that identified extensional deformations along a vertical axis of symmetry and contractions around the waist of the explosion as a cause of damage. Such deformations can be seen in the hydrodynamic flow in frames 5–7 in Figure 1.…”
Section: An Explosion Source Model Accounting For Source Medium Damagementioning
confidence: 99%
“…Long‐period surface waves from the 2006 explosion were larger than expected for an explosion of such low yield. Patton and Taylor [2008] suggested that the high surface wave magnitude, M S , for the 2006 explosion could have resulted from stronger Rayleigh wave radiation due to the absence of spall (tensile failure) at depth as a consequence of the test being conducted in strong material such as granite. Bonner et al [2008] demonstrated that the 2006 event is not clearly screened from earthquakes with the M S : m b (surface wave to body wave magnitude) discriminant and also showed that accounting for the strong (high wave speed) emplacement conditions brings the yield estimated from M S closer to that inferred from m b .…”
Section: The 2006 and 2009 Dprk Nuclear Testsmentioning
confidence: 99%
“…However, in a number of studies (KIM and RICHARDS, 2007;KVAERNA et al, 2007;KOPER et al, 2007;ZHAO et al, 2008) using high-frequency spectral ratios of regional P-and S-wave signals that were archived from previous small earthquakes, the event of October 9, 2006, was identified as an explosion with very high confidence. PATTON and TAYLOR (2008) present an explosion model where tensile failure of surface layers is completely suppressed to explain the poor performance of the teleseismic m b -M s discriminant for the North Korean test. In order to check the IDC and USGS localization, which was mainly based on teleseismic data, waveform data of stations in the regional distance range were examined for onsets of regional seismic waves.…”
Section: Detection Identification Locationmentioning
confidence: 99%